Malaysia-Indonesia: narasi lintas budaya dan negara - Muhammad Febriansyah; Haris Zuan (Petaling Jaya : Strategic Information and Research Development Centre, 2021)
Collection of essays on intercultural relations between Malaysia and Indonesia.
PS-Ashe Enterprise Sdn Bhd/En. Shahruddin Shafri/Ketua Perpustakaan ATMA/NMarina/OC-02/06/2022
Keywords: International relations and culture -- Malaysia; Malaysia -- Foreign relations -- Indonesia; Malaysia -- Cultural relations -- Indonesia; Malay essays; International relations